Differential Effects of Continuous Exposure to the Investigational Metastin/Kisspeptin Analog TAK-683 on Pulsatile and Surge Mode Secretion of Luteinizing Hormone in Ovariectomized Goats - TANAKA, Tomomi (The Society for Reproduction and Development, 2013)
The aim of the present study was to determine if the estradiol-induced luteinizing hormone (LH) surge is influenced by the constant exposure to TAK-683, an investigational metastin/kisspeptin analog, that had been established to depress the pulsatile gonadotropin-releasing hormone (GnRH) and LH secretion in goats. Ovariectomized goats subcutaneously received TAK-683 (TAK-683 group, n=6) or vehicle (control group, n=6) constantly via subcutaneous implantation of an osmotic pump. Five days after the start of the treatment, estradiol was infused intravenously in both groups to evaluate the effects on the LH surge. Blood samples were collected at 6-min intervals for 4 h prior to the initiation of either the TAK-683 treatment or the estradiol infusion, to determine the profiles of pulsatile LH secretion. They were also collected at 2-h intervals from –4 h to 32 h after the start of estradiol infusion for analysis of LH surges. The frequency and mean concentrations of LH pulses in the TAK-683 group were remarkably suppressed 5 days after the start of TAK-683 treatment compared with those of the control group (P<0.05). On the other hand, a clear LH surge was observed in all animals of both groups. There were no significant differences in the LH concentrations for surge peak and the peak time of the LH surge between the TAK-683 and control groups. These findings suggest that the effects of continuous exposure to kisspeptin or its analog on the mechanism(s) that regulates the pulsatile and surge mode secretion of GnRH/LH are different in goats.